Pengaruh Life-Cycle Perusahaan terhadap Incremental Value-Relevance Informasi Laba - Abd. Hamid Habbe (Universitas Muhammadiyah Yogyakarta, Indonesia, 2002)
The main objective of this paper is to examine the effect of life-cycle of firm on the relationship between earnings information and market value of equity. This research is based on inconsistency of the result previous research. I derive hypothesis from Myers theory (1997) which imply that the value of the firm is determined by two components, value of asset in place and growth opportunities. These two components have a difference characteristic in each phase of life-cycle. I employ common factor analysis to classify sample into five phases, growth phase, growth/maturity phase, maturity phase, maturity/stagnant phase, and stagnant phase. The result is consistent with hypothesis that each phase of life-cycle (except growth phase), earnings is positive relation to market value of equity. In addition, I also find evidence a various determination of earnings in each phase. This result indicate that firm life-cycle provide incremental value relevance for earnings information.